Dynamic evaluation of conditional survival in patients with oral squamous cell carcinoma after surgical resection: A large-scale prospective study. (May 2020) - Yan, Lingjun; Chen, Fa; Chen, Lin; Lin, Jing; Chen, Qing; Bao, Xiaodan; Qiu, Yu; Lin, Lisong; Zheng, Xiaoyan; Pan, Lizhen; Wang, Jing; Hu, Zhijian; et al.
Highlights: Conditional survival (CS) estimates is a novel approach to provide a dynamic vision for oral cancer patients' prognosis. The 3-year CS showed a tendency to increase over time, while the actuarial OS rates decreased with time. The impacts of unfavorable tumor features declined over time, despite the high risk at initial diagnosis. Abstract: Objective: To dynamically estimate conditional survival (CS) probabilities for patients with oral squamous cell carcinoma (OSCC) after surgical resection. Method: A large-scale prospective study was performed involving 1147 eligible OSCC patients from December 2002 to June 2018. Follow-up was completed on January 8, 2019. Cox proportional hazards models were utilized to assess prognostic factors related to overall survival (OS). Three-year CS (CS3 ) of patients who had already survived x years was calculated as the formula CS3 = OS(x+3) /OS(x). Results: CS3 estimates at the time of 0, 1, 3, 5-year survival demonstrated a tendency increase over time, and improved from 78.47% to 82.25%, while the postoperative actuarial OS decreased from 78.47% at 3 years to 57.12% at 8 years. Moreover, the differences between CS3 and actuarial OS were more obvious among patients with unfavorable tumor characteristics. Disparities in CS3 across all subgroups of tumor features illustrated more prominent at baseline (d range: 0.24 to 0.40), while the gaps would narrow if those patients have already survived 5 years (d range: −0.01 to 0.18). Conclusion: Our findings suggest that survival profiles of OSCC patients evolve and increase over time following resection, especially for those with unfavorable tumor features at initial diagnosis. CS estimates may provide more accurate prediction and guide surveillance schedules.